1980
DOI: 10.1152/jappl.1980.49.5.881
|View full text |Cite
|
Sign up to set email alerts
|

Body acceleration distribution and O2 uptake in humans during running and jumping

Abstract: Body acceleration distribution and its relation to the mode of generation were determined in eight young males (19-26 yr) who walked and ran on a treadmill operated at four speeds and jumped on a trampoline at four heights. With increasing treadmill speed, peak acceleration at the ankle (Aa = 3.0-12.0 Gz) always exceeded that at the back and forehead (Ab = 0.9-5.0 Gz, and Ah = 0.8-3.9 Gz); these acceleration profiles included higher frequency components than those during jumping. Corresponding ranges of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
3
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 0 publications
2
45
3
3
Order By: Relevance
“…Higher frequencies are caused by the impact between foot and walking surface and do not directly result from voluntary muscular work. By using piezoresistive accelerometers (range: 20 g, frequency response: 0-70 Hz), taped to the skin, Bhattacharya et al [28] found the majority of frequency components during running to vary between 1-18 Hz in vertical direction at the ankle. At the low back and the head, the frequency content of acceleration profiles was smaller.…”
Section: Human Body Accelerationmentioning
confidence: 99%
“…Higher frequencies are caused by the impact between foot and walking surface and do not directly result from voluntary muscular work. By using piezoresistive accelerometers (range: 20 g, frequency response: 0-70 Hz), taped to the skin, Bhattacharya et al [28] found the majority of frequency components during running to vary between 1-18 Hz in vertical direction at the ankle. At the low back and the head, the frequency content of acceleration profiles was smaller.…”
Section: Human Body Accelerationmentioning
confidence: 99%
“…However, the human-activity frequency range is much lower than the sampling band chosen. By using accelerometers taped to the body while running, Bhattacharya, McCutcheon, Shvartz, and Greenleaf (1980) found the main frequency components between 1-18 Hz at the ankle. As will be seen later, our work proposes placing the device at the hip, where acceleration forces are lower than at the ankle, and hence frequencies at this position are also lower.…”
Section: Embedded Sensors and Battery Impactmentioning
confidence: 99%
“…La aceleración aumenta en magnitud de la cabeza a los tobillos. Correr produce las aceleraciones mayores en la dirección vertical de 8,1 -12 g en el tobillo [35][36][37][38][39][40][41][42][43][44] , hasta 5,0g en la parte lumbar [35][36][37][38][39][40][41][42][43][44] y hasta 4,0 en la cabeza 44 . Las aceleraciones del tronco en el eje vertical que se han obtenido durante la marcha abarcan el rango -0,3 a 0,8 g, mientras que en dirección horizontal medido en la zona lumbar el rango va de -0,3 a 0,4 g y de -0,2 a 0,2 en la cabeza 45 .…”
Section: Acelerómetros Y Giróscopos Aplicados a La Monitorización Delunclassified
“…Es la tarea que requiere el mayor esfuerzo mecánico dentro de las actividades cotidianas 44,59 y es un prerrequisito para poder caminar 60 . La capacidad de sentarse de forma controlada posee igual importancia.…”
Section: Movimiento De Sentarse Y Levantarseunclassified